Tourism development within planning paradigms: The case of Turkey - Alipour, H (Butterworth-Heinemann Ltd, 1996)
The focus of this study is to examine the Turkish government's policy and planning process that was directly or indirectly involved in tourism development with the major aim of identifying the variables that are at work within the tourism organizations and administrative system, A case study of planning and implementation processes suggests that Turkey's tourism development was subject to various deliberate influences and spontaneous dynamics without a proactive national tourism policy, Furthermore, the planning process has remained limited to physical planning to the detriment of social, environmental and integrated planning, The tourism industry is confined to a few enclave developments as directed by market forces rather than as a derivative of formal planning decisions, This study also acknowledges that a 'planning' paradigm for tourism has been established, but not necessarily adopted/applied in every tourism development project (particularly in Turkey). Copyright (C) 1996 Elsevier Science Ltd
Keywords: tourism planning; policy analysis; development; implementation